The transformation of the sacred meaning of Sepilar Temple Malang through symbolic interaction between generations - Syafi’uddin, Syafi’uddin; Tualeka, Muhammad Nur Wahid; Anam, Khoirul (Universitas Muhammadiyah Malang, 2026)
The transformation of sacred meaning is shaped not only by technological developments but also by processes of interpretation that occur through social interaction. This article examines how the sacred meaning of Candi Sepilar in East Java is constructed and negotiated across generations within the context of digital representation. The study employs a qualitative approach with an interpretive paradigm and draws on the framework of symbolic interactionism to understand how social actors interpret symbols, spaces, and practices associated with sacredness. Data were collected through field observations, in-depth interviews with traditional custodians and members of Generation Z, and an analysis of fourteen TikTok posts representing Candi Sepilar. The data were analyzed using a thematic-interpretive approach to explore the processes through which meanings are produced and negotiated in everyday social practices. The findings indicate that the older generation interprets Candi Sepilar as a spiritual space connected to cosmological relationships between humans, ancestors, and nature, maintained through ethical norms and ritual practices. In contrast, the younger generation tends to interpret the site through reflective experiences, historical value, and visual representations mediated by social media. Interaction between the two generations does not result in a conflict of meanings but instead generates processes of symbolic negotiation that allow multiple interpretations of sacredness to coexist. These findings reveal a form of sacredness that can be understood as hybrid sacredness, a configuration of sacred meaning that is preserved through ethical norms and local cultural memory while simultaneously being represented through digital media within intergenerational interaction. Transformasi makna sakral tidak hanya dipengaruhi oleh perkembangan teknologi, tetapi juga oleh proses interpretasi makna yang berlangsung melalui interaksi sosial. Artikel ini menganalisis bagaimana makna kesakralan Candi Sepilar di Jawa Timur dikonstruksi dan dinegosiasikan lintas generasi dalam konteks representasi digital. Penelitian ini menggunakan pendekatan kualitatif dengan paradigma interpretatif dan kerangka interaksionisme simbolik untuk memahami bagaimana aktor sosial memaknai simbol, ruang, dan praktik yang terkait dengan kesakralan. Data diperoleh melalui observasi lapangan, wawancara mendalam dengan penjaga tradisi dan generasi muda (Gen Z), serta analisis terhadap empat belas unggahan TikTok yang merepresentasikan Candi Sepilar. Analisis dilakukan secara tematik-interpretatif untuk menelusuri proses produksi dan negosiasi makna dalam praktik sosial sehari-hari. Hasil penelitian menunjukkan bahwa generasi tua memaknai Candi Sepilar sebagai ruang spiritual yang terkait dengan relasi kosmologis antara manusia, leluhur, dan alam yang dipertahankan melalui norma etika dan praktik ritual. Sebaliknya, generasi muda cenderung memaknai ruang tersebut melalui pengalaman reflektif, nilai sejarah, dan representasi visual yang dimediasi oleh media sosial. Interaksi antara kedua generasi tidak menghasilkan konflik makna, tetapi membentuk proses negosiasi simbolik yang memungkinkan berbagai interpretasi kesakralan hidup berdampingan. Temuan ini menunjukkan bentuk kesakralan yang dapat dipahami sebagai sakralitas hibrid, yaitu konfigurasi makna sakral yang dipertahankan melalui norma etika dan memori budaya lokal sekaligus direpresentasikan melalui medium digital dalam interaksi lintas generasi.